Synthesis and characterization of highly fluorinated sulfonated polytriazoles for proton exchange membrane application. Issue 16 (2nd February 2016) - Singh, Asheesh; Banerjee, Susanta; Komber, Hartmut; Voit, Brigitte
Abstract : A series of polytriazole copolymers were synthesized by the click polymerization of fluorinated dialkyne with a mixture of two different diazide monomers and the proton exchange membrane properties of the copolymers were investigated. Abstract : A series of polytriazole copolymers (PTFQSH- XX ) were synthesized by the click polymerization of 1, 1, 1, 3, 3, 3-hexafluoro-2, 2-bis(4-(prop-2-ynyloxy)phenyl)propane (TF) with a mixture of two diazide monomers: 4, 4-bis[3-trifluoromethyl-4(4-azidophenoxy)phenyl]biphenyl (QAZ) and 4, 4′-diazido-2, 2′-stilbene disulfonic acid disodium salt ("S"). The degree of sulfonation (DS) of the copolymers was controlled by adjusting the mole ratio of "S" to the non-sulfonated diazide (QAZ). The polytriazole copolymers were characterized by FTIR and NMR ( 1 H, 13 C and 19 F) spectroscopy. The PTFQS- XX membranes were prepared by dissolving the salt form of the copolymers in dimethyl formamide. The physical properties and proton conductivity of the membranes were investigated. The presence of hexafluoroisopropylidene groups in the copolymers contributed to high thermal and oxidative stability and low swelling of the membranes. TEM micrographs of the polytriazole membranes showed a good phase separated morphology with ionic clusters in the range of 3–75 nm. The proton conductivities of the fluorinated membranes were found in the range of 27–136 mS cm −1 at 80 °C in water.